Structural analysis of dextran-based hydrogels obtained chemoenzymatically - Ferreira, L. (2006)
This work reports the results of structural analysis in novel dextran-acrylate (dexT70-VA) hydrogels generated chemoenzymatically. Porous structure as well as hydrogel surface and interior morphologies were evaluated by mercury intrusion porosimetry (MIP), nitrogen adsorption (NA), and scanning electron microscopy (SEM) analyses, as a function of the degree of substitution (DS), and initial water content used in the preparation of the hydrogel. MIP analysis showed that the overall networks were clearly macroporous with pore sizes ranging from 0.065 to 10 mum. As expected, the average pore size decreased as DS increased and as initial water content decreased. Moreover, the porosity values ranged from 75 up 90%, which shows that these hydrogels present an interconnected pore structure. Nitrogen adsorption analyses showed that the specific surface area of dexT70-VA hydrogels increased either by increasing the DS or by decreasing the initial water content of the hydrogel. SEM results revealed that the surface of hydrogels with lower DS presented either a porous structure or a polymeric ldquoskinrdquo covering the pores, whereas hydrogels with higher DS were totally porous. Furthermore, the interior morphology varied according to the DS and the initial water content of the hydrogels. Finally, the average pore size was also determined from the swelling of hydrogel using a theoretical model developed by Flory-Rehner. The comparison of the SEM and MIP results with the ones obtained by the equilibrium swelling theory of Flory-Rehner shows that this approach highly underestimates the average pore size. © 2005 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2006